Social Organisation of the Short-finned Pilot Whale, Globicephala macrorhynchus, with Special Reference to the Comparative Social Ecology of Delphinids - Heimlich-Boran, James Robert (University of Cambridge, Department of Zoology, 1993)
As a contribution to the understanding of comparative social trends within the cetacean family Delphinidae, a 22-month study was conducted on the shortfinned pilot whale, Globicephala macrorhynchus, which has been suggested to have a unique social system in which males and females in the same group are related and mating occurs outside of the group. The individual identification of 495 pilot whales, analysed in daily group association patterns, allowed identification of 46 pods. They were classified as productive or non-productive based on the presence or absence of immature animals. Productive pods were a significantly larger, although 12% of them lacked adult males. Two classes of whales (residents and visitors) were defined by patterns of occurrence,suggesting differential patterns of habitat use. Resident pods occasionallytravelled together (41% of all groups) and associations between age and sex classes showed that in mixed-pod groups, the highest ranked associations of thereproductive females were with males from other pods, while within pods, adult males and females associated less. During summer, the proposed peak conception period, pilot whale groups were significantly larger and containedindividuals from a significantly greater number of pods. These findings support the hypothesis that males and females mate when associating with individuals from other pods. A comparative analysis of sexual dimorphism, brain size, and testes size, habitat, prey and group size within the 17 delphinid genera identified a correlation between sexual dimorphism and body size, but relative measures ofbrain size and testes size did not correlate with broad ecological or social classifications. However, a comparison of three delphinid societies identified two distinct male mating systems: males of the small, mono-morphic Tursiopstruncatus live in age/sex segregated groups and mate with a number of discrete female communities. Males in the large sexually dimorphic Glob icephala spp. and Orcinus orca mate with associated female ...